RIVAROXABAN IN PATIENTS STABILIZED AFTER A ST-SEGMENT ELEVATION MYOCARDIAL INFARCTION. RESULTS FROM THE ATLAS ACS-2–TIMI-51 TRIAL - J. L. Mega; E. Braunwald; S. A. Murphy; A. N. Plotnikov; P. Burton; R. G. Kiss; A. Parkhomenko; M. Tendera; P. Widimsky; C. M. Gibson (Рациональная фармакотерапия в кардиологии)
.